Market premia for renewables in Germany: The effect on electricity prices - Frondel, Manuel; Kaeding, Matthias; Sommer, Stephan (Technische Universität Dortmund, 2020)
Due to the growing share of ”green” electricity generated by renewable energy technologies, the frequency of negative price spikes has substantially increased in Germany. To reduce such events, in 2012, a market premium scheme (MPS) was introduced as an alternative to feed-in tariffs for the promotion of green electricity. Drawing on hourly day-ahead spot prices for the time period spanning 2009 to 2016 and employing a nonparametric modeling strategy called Bayesian Additive Regression Trees, this paper empirically evaluates the efficacy of Germany’s MPS. Via counterfactual analyses, we demonstrate that the introduction of the MPS decreased the number of hours with negative prices by some 70%.
Discussion Paper / SFB823;13/2020
Keywords: egative electricity prices; Bayesian additive regression trees; merit order effect; 310; 330; 620